Correlation of Platelet to Lymphocyte Ratio and C-Reactive Protein to Albumin Ratio with MEX-SLEDAI Scores in Patients with Systemic Lupus Erythematosus - Amelia, Rachel; Wasilah, Fajar; Suraya, Nida Suraya (Althea Medical Journal, 2024)
Background: One of the methods used to assess systemic lupus erythematosus (SLE) disease activity is the Mexican systemic lupus erythematosus disease activity index (MEX-SLEDAI) score. Markers of SLE  disease activity such as anti-dsDNA antibodies, complement, and anti C1q  have limitations in terms of sensitivity and specificity.  In rural areas where these markers are not available, simpler alternative markers are valuable. This study aimed to explore markers related to SLE disease activity based on the platelet to lymphocyte ratio (PLR) and C-reactive protein albumin ratio (CAR) using the MEX-SLEDAI score.Methods: This was a cross-sectional study using a correlational analytical design. Data collection was carried out retrospectively using secondary data taken from medical records of patients with SLE treated at Dr. Hasan Sadikin General Hospital Bandung, Indonesia in 2019–2021 and the Laboratory Information System (LIS). The data was analyzed using the Spearman rank correlation test.Results: Of the 51 participants, 92% were female with median MEX-SLEDAI scores of 9. The median value of PLR and CAR were 247.07 and 2.01, respectively. The CAR showed a moderate positive correlation (r=0.563, p<0.001), whereas the PLR showed no correlation (r=0.023, p>0.05) with the MEX-SLEDAI score.Conclusions: MEX-SLEDAI scores has a moderate positive correlation with CAR, suggesting that CAR may be used as a marker in assessing disease activity in adult patients with SLE.